The Privacy Paradox in Smart Classrooms: Balancing Data-Driven Personalization with Student Data Protection and Ethical Governance - Rit Som; Pierre Ndayizeye; Alida Ntahonkiriye (Journal Emerging Technologies in Education, 2026)
Background: The integration of smart technologies in classrooms has significantly enhanced personalized learning by utilizing data analytics to cater to individual student needs. However, the increasing reliance on student data has raised concerns about privacy, security, and ethical governance, creating what is known as the "privacy paradox." This paradox reflects the tension between the benefits of data-driven personalization and the need to protect student privacy. Purpose: This study aims to explore the privacy paradox in smart classrooms, examining how educational institutions balance the benefits of personalized learning with the ethical responsibilities of student data protection. The research investigates the perceptions of students, teachers, and administrators regarding data privacy and governance practices in smart classrooms. Method: A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews with 200 participants, including students, teachers, and administrators from higher education institutions that use smart classroom technologies. The survey assessed privacy concerns, while interviews provided deeper insights into the ethical dilemmas and data governance practices. Results: The findings revealed a significant gap between students’ concerns about privacy and the confidence administrators had in data protection measures. Students expressed high concern over their data, whereas administrators were more confident in their institution’s data governance, highlighting a lack of transparency. Conclusion: The study underscores the need for improved transparency and ethical governance in smart classrooms to address privacy concerns. Effective data protection policies and communication are essential to balancing data-driven personalization with student privacy.